2014
DOI: 10.18202/jamal.2014.12.5029
|View full text |Cite
|
Sign up to set email alerts
|

“Kamuflase” dalam Praktik Rotasi Auditor

Abstract: Abstrak: "Kamuflase" dalam Praktik Rotasi Auditor. Penelitian ini bertujuan menemukan makna praktik rotasi auditor dari perspektif auditor. Melalui metode fenomenologi transendental Husserl, ditemukan bahwa rotasi auditor memiliki tujuan mulia di antaranya untuk menjaga dan meningkatkan independensi auditor, kualitas audit, sharing knowledge and profit, serta mencegah terjadinya kolusi antara auditor dengan klien. Di sisi lain, adanya ketergantungan ekonomis auditor pada klien mengakibatkan adanya praktik "kam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Irianto, Novianti, & Wulandari (2014) explain that there are three steps that need to be done in phenomenology method, namely phenomenological reduction, eidetic reduction, and transcendental reduction. In phenomenological reduction, the researcher attempts to find and classify the meaning of statements felt by informants by doing horizonalization ie checking the data and highlighting various "important statements", sentences, or quotes that provide an understanding of how participants experience accounting phenomena (Creswell, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Irianto, Novianti, & Wulandari (2014) explain that there are three steps that need to be done in phenomenology method, namely phenomenological reduction, eidetic reduction, and transcendental reduction. In phenomenological reduction, the researcher attempts to find and classify the meaning of statements felt by informants by doing horizonalization ie checking the data and highlighting various "important statements", sentences, or quotes that provide an understanding of how participants experience accounting phenomena (Creswell, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In phenomenological reduction, the researcher attempts to find and classify the meaning of statements felt by informants by doing horizonalization ie checking the data and highlighting various "important statements", sentences, or quotes that provide an understanding of how participants experience accounting phenomena (Creswell, 2015). Furthermore, eidetic reduction aims to find the eidos or hidden essence or meaning of the observed phenomenon (Irianto et al 2014, in which the researchers combine textual descriptions (informant experiences) and structural descriptions (research contexts that can be produced). this study is a transedental reduction, in which the aim is to discover the true or pure and intact nature or meaning (Irianto et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stages of data analysis in this study using the stages suggested by Creswell (2015) that has developed the pattern of Moustakas (1994). Irianto, Novianti, & Wulandari (2014) explain that there are three steps that need to be done in phenomenology method, namely phenomenological reduction, eidetic reduction, and transcendental reduction. In phenomenological reduction, the researcher attempts to find and classify the meaning of statements felt by informants by doing horizonalization ie checking the data and highlighting various "important statements", sentences, or quotes that provide an understanding of how participants experience accounting phenomena (Creswell, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, eidetic reduction aims to find the eidos or hidden essence or meaning of the observed phenomenon (Irianto et al 2014, in which the researchers combine textual descriptions (informant experiences) and structural descriptions (research contexts that can be produced). this study is a transedental reduction, in which the aim is to discover the true or pure and intact nature or meaning (Irianto et al, 2014).…”
Section: Methodsmentioning
confidence: 99%